Efektivitas metode Talking Stick pada Mata PelajaranIlmu Pengetahuan Sosial (IPS) Materi Keunggulan IklimDi indonesia kelas VIII SMP muhammadiyah 2 Surakarta - Azhary, Agung (2016)
The background of this problem is sometimes the teacher is not able to control the classroom atmosphere for elections learning method is less precise, so when learning a lot of students who were noisy and crowded alone or with, the selection method of learning is very necessary in order to be effective classroom and provide maximum results. The purpose of this study to determine the Talking Stick method can be used to assess and describe the results of the climate advantages of learning materials in Indonesia, and knowing the talking stick method is more effective than conventional methods. This research method uses design of experiment with a test Pre - Post test. A class of experiments using the talking stick and grade control using conventional methods. The sample in this study were all students of class VIII SMP Muhammadiyah 2 Surakarta. The results showed an increase in the average - average value of the knowledge and skills of the experimental class compared to the control class. Value - average experimental classes who receive treatment using talking stick method, has a post test values and skills of the average - average bigger, ie 84.12 and 3.6 of the control class that gained value - average 81.6 and 3, 4 who use the lecture method, thus Ho is rejected and Ha accepted. The difference of these two